Den enigmatiske „Brune Dreng“ på Rosenholm i nyt lys - Heimbürger, Minna (Historisk Tidsskrift, 2018)
A Fresh View of the Enigmatic „Brown Boy“ at Rosenholm One of the treasures of 17th century portrait painting in Danish museums is „The brown Boy“, a full-length figure of a boy dressed completely in brown. The painting is now on loan to Rosenholm Castle, from the Museum of Frederiksborg in Hillerød. Surprisingly and sadly, the identities of the represented person and of the painter are not known. While the names of Axel Rosenkrantz and Abraham Wuchters have been proposed, respectively, these are just hypotheses without documentation. Historians and art historians remain unconvinced. The attribution to Wuchters was rejected by the late historian Povl Eller, who studied the canvas and discussed it in his 1971 doctoral thesis. A couple of years later, he mentioned the picture again and suggested that, „More likely it has been executed abroad.“ Eller continued with an appeal to other Danish scholars: ‘It should be an essential task to have the matter resolved or simply have it better illuminated.’ This is the goal of the current work, almost half a century later. A coat of arms figures on the canvas; this was added in a later period, and indicates that the boy represented must be one of the barons of Rosendal (in Norway), which in the 17th century belonged to the Boller branch of the Rosenkrantz family. The lives and careers of Axel Rosenkrantz and his three elder brothers seem to exclude all of them as models of the portrait, leaving their father, Ludvig Rosenkrantz (1628–1685), who founded the barony in 1678, as the only possibility. It must be he who had the coat of arms added to the portrait from his boyhood, which most probably was painted in the late 1630s, after his father‘s death, while he was living with his mother and his younger brother in the Netherlands. Stylistic, chromatic and compositional analyses of the picture testify that its author hailed from the Flemish-Dutch painting schools from just before the middle of the century. International art historians have ruled out the possibility of a Dutch or Flemish artist as the author of the painting, yet Abraham Wuchters (1608–1682) was born in Antwerp and is documented to have married and lived in Holland until 1638, when he was appointed court painter to Christian IV and immigrated to Denmark. It is proposed that Wuchters met the Rosenkrantz family in the Netherlands and painted Ludvig when the future baron was about eight years old.